Aboriginal Peoples Survey, 2006 [Canada]: Children and Youth - Statistics Canada. Social and Aboriginal Statistics Division. (Borealis, 2009)
The Aboriginal Peoples Survey provides data on the social and economic conditions of First Nations people living off reserve, Métis and Inuit, aged 6 years and older.